Hicrî II. Asır Ehl-İ Hadîs halkaları (Basra örneği) - Maden, Ömer Faruk (My University, 2018)
Diğer İslâmî ilimlerde olduğu gibi hadis ilminin teşekkülünde de önemli bir yeriolan Basra, hicrî 2. asrın en önemli ilim merkezlerinden biridir. Bu açıdan Basra’nınilmî yapısının tespiti hadis tarihinin anlaşılmasına katkıda bulunacaktır. Bu çalışmadagenel olarak hicrî 2. asırda Basra’nın durumuna, özel olarak ise mezkur zamandiliminde Basra’da ön plana çıkan dört ana hadis halkasına dair tespitler bulunmaktadır.Bunlar sırasıyla İbn Sîrîn, Hasan el-Basrî, Sâbit el-Bünânî ve Yahya b. Ebû Kesîrhalkalarıdır. İbn Sîrîn ve Hasan el-Basrî halkaları diğerlerine nazaran daha fazla önplana çıkmıştır. Halkalar, üyelerinin birbiriyle ilişkisi ve genel özellikleri dikkatealınarak incelenmiştir. Böylece hadis ilminin hicrî 2. asırda Basra’daki durumu tespitedilmeye çalışılmıştır.

Basra, one of the most prominent centers of Islamic studies in the secondcentury of Hijrah, has played a great role in the formation of the science of Hadithbeside other Islamic sciences. For that matter, studying the scientific situation of Basrawill help comprehend the historical developments of the science of Hadith. The mainaim of this study is to analyze, in general, the situation of Basra in the second century ofHijrah, and in particular, four scholarly circles which has come into prominence at thattime. These are, in descending order of importance, circles of Ibn Sîrîn, Hasan el-Basrî,Sâbit el-Bünânî and Yahya b. Ebû Kesîr. Circles of Ibn Sîrîn and Hasan el-Basrî aremore outstanding as compared with the others. These mentioned circles have beenstudied by taking into account their general characteristics and the relations betweentheir members. Thus, the aim is to scrutinize the situation of the science of Hadith in thesecond century of Hijrah in Basra.
Keywords: Basra; Hadis; Hadith; halka; Hasan el-Basrî; History; Islam religion; Islamic sciences; İbn Sîrîn; İslam dini; İslami ilimler; Sâbit el-Bünânî; scholarly circle; Tarih; Yahya b. Ebû Kesîr; Yahya b. Ebû Kesîr Basra